Nucula Lamarck 1799 ... - Kiel, Steffen; Sami, Marco; Taviani, Marco (Zenodo, 2023)
Genus Nucula Lamarck, 1799 Type species Arca nucleus Linnaeus, 1758, by monotypy. ... : Published as part of Kiel, Steffen, Sami, Marco & Taviani, Marco, 2023, Mollusks (Gastropoda, Bivalvia) from Miocene cold-seep deposits in northern Italy: revisions and additions, pp. 115-160 in European Journal of Taxonomy 910 on page 138, DOI: 10.5852/ejt.2023.910.2365, http://zenodo.org/record/10350702 ...